Oral History Program Interview: Edgar Combs - Combs, Edgar
Born in Virginia in 1894, Combs would come to Bakersfield, California on March 30, 1917 and settle in Arvin. Combs's perspective as a grower provides an interesting look at the migrants and issues farmers faced. This interview depicts tent and ditch camps, the kinds of housing he provided for his workers, why he avoided employing government camp inhabitants, how Californians viewed the border patrols, cotton strikes in 1933 and 1938, claims the origins of the term "Okie" and "Arkie" were from the migrants themselves, and that small farmers not much better off than migrants.